The Effects of Gedi Leaf on the Labor Process in Women Who Have the Habit of Consuming Areca Nuts - Cory Chorajon Situmorang; Ni Nyoman Sri Artina Dewi (Universitas Andalas, 2021)
Betel leaves and areca nut can form excessive connective or fibrous tissue in the submucosa. At the end of pregnancy, due to aging of the placenta, there is also a decrease in the estrogen which can affect the volume of cervical mucus which is used as an emulsifier for the delivery process to help the elasticity of the vagina and perineum. The purpose of this study was to determine the difference in the duration of labor in the first stage of labor in women with the habit of consuming areca nut with addition of gedi leaves and without gedi leaves. This was a preexperimental reserach in the form of intact group comparison. A sample of 28 people was divided into the experimental group (which was treated) and the control group (which was not treated). The study was carried out at the Melati Raya Health Center which is an auxiliary health center at the Remu Health Center, Sorong City, West Papua in August-November 2020. The results of the analysis used an independent T test showed a p value of 0.027 < 0.05, meaning Ha was accepted and Ho was rejected. It was therefore concluded that the consumption of gedi leaves can accelerate the process of labor in the active phase for those who consume betel leaves and areca nuts at the Remu Health Center, Sorong City.